Digital Literacy: a New Culture of Learning in the Era of Digitalization Through Cyber Pedagogy Strategies - Herwani, Suci; Pasiningsih, Pasiningsih (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2023)
The Covid-19 pandemic that occurred in Indonesia requires organizers interested in the world of education to have the ability to be creative and innovative so that learning continues. One way is to use technology in learning, one of them online learning. Online learning is different from face-to-face learning then the right strategy is needed so that learning can be understood by learners. Learning that is based on and uses internet media is called digital literacy-based learning, one of which uses Cyber Pedagogy. This strategy are designing, implementing, and evaluating the interactions that occur in cyber learning. The purpose of this study is to describe digital literacy in learning in the era of digitalization through Cyber Pedagogy. The research method used is literature study using a qualitative descriptive approach. The results research showed that Cyber Pedagogy strategies can help learners to think critically about the material obtained from the platforms on technology devices.